Isolation of cDNAs Encoding Asparagine Synthetase from Coronilla rostrata - Artanti, Nina; McFarlane, James (BRIN, 2012)
Asparagine synthetase (AS) is one of the enzyme involves in ammonium metabolism in plant, it catalyzes the transfer of the amino group of glutamine to aspartate giving asparagine. Asparagine serves as a major nitrogen transport and storage molecule in many higher plants. This research used legume plant Coronilla rostrata callus culture for primary and secondary metabolism study. On primary metabolism, the culture were used to study the phenomenon of asparagine accumulation. Because of the responsiveness of the culture, we investigated the use of this culture for model system to conduct molecular biology study of the nitrogen metabolism. The aim of this study was to isolate cDNAs enconding asparagine synthetase from C. rostrata because of the asparagine accumulate in this culture. Several PCR based approaches were conducted such as RT-PCR, LM-PCR, and RACE. Using these methods, two AS cDNAs was isolated from C. rostrata AS1 (GenBank no AY081945) which a complete cDNA sequence and AS2 which a partial cDNA sequence. (GenBank no AF488726). These two cDNAs had high homology with the legume AS.